Amino acid and fatty acid profile of whole-dried and minced-dried fish discards (Leiognathus sp.) from shrimp trawl fishery in Jaffna, Sri Lanka - Saruga, K.; Sivashanthini, K.; Ragnar, L.; Olsen (University of Jaffna, 2023)
The by-catch and discards from shrimp trawl fishery have increased during the last few years. Leiognathus sp. is one of the most discarded fish species in the shrimp trawling fishery in Jaffna, Sri Lanka. Lack of information was found regarding the nutrient composition of Leiognathus sp. and therefore the present study was carried out to assess the presence of amino acids and fatty acids in whole-dried and mince-dried fish which are beneficial for human health. The total sum of amino acids was estimated to be 229.8 and 174.4 mg/g raw protein percentages in whole-dried fish and minceddried fish, respectively. The protein content of fish is mainly explained by the sum of the total amino acids identified. The total lipid was 5.5% and 7.3% in whole-dried fish and minced-dried fish, respectively. Proline and glycine were found to be the abundant amino acids in both whole-dried and minced-dried fish. A total of 13 fatty acids in whole-dried fish and 14 fatty acids in minced-dried fish were identified in the present study. The n-3 polyunsaturated fatty acids were found to be one of the highly abundant compounds in this fish and docosahexaenoic acid is also considerably higher in amount. In the sense of higher availability of protein, storage of whole-dried fish will be a better option than minced-dried fish. Drying is one of the best and easiest methods to preserve this fish and dried fish products could be supplied to the local population at a low cost to overcome the nutrient deficiency among them. Alternatively, utilizing these bycatch fish is an effective method to reduce marine pollution as well.
Keywords: Amino acids; Discards; Fatty acids; Leiognathus sp; Shrimp trawling